Short-range organization and photophysical properties of CdSe quantum dots coupled with aryleneethynylenes. (4th June 2022) - Theurer, Christoph P; Weber, Antonia; Richter, Martin; Bender, Markus; Michel, Patrick; Rana, Debkumar; Kumar, Krishan; Bunz, Uwe; Scheele, Marcus; Tegeder, Petra; Schreiber, Frank; Broch, Katharina
Abstract: Hybrid organic–inorganic nanomaterials composed of organic semiconductors and inorganic quantum dots (QDs) are promising candidates for opto-electronic devices in a sustainable internet of things. Especially their ability to combine the advantages of both compounds in one material with new functionality, the energy-efficient production possibility and the applicability in thin films with little resource consumption are key benefits of these materials. However, a major challenge one is facing for these hybrid materials is the lack of a detailed understanding of the organic–inorganic interface which hampers the widespread application in devices. We advance the understanding of this interface by studying the short-range organization and binding motif of aryleneethynylenes coupled to CdSe QDs as an example system with various experimental methods. Clear evidence for an incorporation of the organic ligands in between the inorganic QDs is found, and polarization-modulation infrared reflection-absorption spectroscopy is shown to be a powerful technique to directly detect the binding in such hybrid thin-film systems. A monodentate binding and a connection of neighboring QDs by the aryleneethynylene molecules is identified. Using steady-state and time resolved spectroscopy, we further investigated the photophysics of these hybrid systems. Different passivation capabilities resulting in different decay dynamics of the QDs turned out to be the main influence of the ligands on the photophysics.